Structural Engineering of Cobalt‐Free Perovskite Enables Efficient and Durable Oxygen Reduction in Solid Oxide Fuel Cells. Issue 6 (24th April 2022) - Dong, Feifei; Ma, Zilin; Ye, Qirui; Zhang, Bingkai; Li, Lu; Yang, Guangming; Ni, Meng; Lin, Zhan
Abstract: Developing low‐cost, efficient, and durable cobalt‐free perovskite oxides for oxygen reduction reaction at intermediate‐to‐low temperatures is crucial to enhance the viability of solid oxide fuel cells (SOFCs), a promising ingredient for establishing a more sustainable future. Herein, a highly active and robust cobalt‐free perovskite Ba0.75 Sr0.25 Fe0.95 P0.05 O3‐δ (BSFP) oxygen electrode via a facile co‐doping strategy for intermediate‐to‐low temperature SOFCs (ILT‐SOFCs) is reported by a combined experimental and theoretical approach. Attributed to stable and oxygen defect‐rich structure, and remarkable intrinsic oxygen transport kinetics, the BSFP cathode shows exceptional catalytic performance, including record‐level power output among iron‐based perovskite cathodes (1464 mW cm –2 at 600 °C), low area‐specific resistance (≈0.1 Ω cm 2 at 600 °C), robust stability both in symmetrical and single cell configurations, and outstanding CO2 tolerance/reversibility. The first‐principle calculations validate the role of co‐doping of strontium and phosphorus for the high activity and durability. Central to this work is the combined experiment‐calculation approach to point to an effective strategy in the development of highly active and stable perovskite‐type cathodes for ILT‐SOFCs and related applications. Abstract : An advanced perovskite Ba0.75 Sr0.25 Fe0.95 P0.05 O3‐δ exhibits exceptional electrocatalytic activity and durability as a novel cobalt‐free cathode for oxygen reduction reaction, as evidenced by experimental and computational tools, representing a significant advancement in developing promising cobalt‐free cathode materials for intermediate‐to‐low temperature solid oxide fuel cells.